RFID-based access control system with a multimedia messaging display board - Lacap, Edward John Santos
The vital need for limiting physical access to an environment housing confidential resources is usually addressed by the implementation of access control systems. Though access control solutions are already available in the market, they are commonly based on proprietary and closed technology and come with high operating cost. We have developed a low-cost access control system by using radio frequency identification devices and off-the-shelf electronic relays both conveniently interfaced to a host PC. In contrast to commercially available access control solutions, our system was implemented on a secure and open platform employing the widely accepted RADIUS as its authentication procedure. We drifted away from the traditional in/out displays by taking full advantage of the user presence information made available by the access control system. We added and organized messaging system that would enable users to manipulate and broadcast their presence information and likewise leave and retrieve multimedia messages through the access control display board. A touch screen display with an enhanced graphical user interface was used to deliver the task of broadcasting the user-manipulated presence information and multimedia messaging.